Trends in human leptospirosis in Denmark, 2012-2021 - Eves, Caroline; Kjelsø, Charlotte; Benedetti, Guido; Jørgensen, Charlotte Sværke; Krogfelt, Karen Angeliki (Frontiers in Cellular and Infection Microbiology, 2023)
Leptospirosis is a zoonotic bacterial infection that can cause influenza-like symptoms and severe disease. In Denmark, leptospirosis is rare, non-endemic, and most commonly transferred to humans from mice and rats. Cases of human leptospirosis in Denmark are by law notifiable to Statens Serum Institut. This study aimed to describe trends in incidence of leptospirosis in Denmark from 2012 to 2021. Descriptive analyses were used to calculate the incidence, geographical distribution and possible routes of infection, as well as testing capacity and serological trends. The overall incidence rate was 0.23 per 100,000 inhabitants, with the highest annual incidence of 24 cases in 2017. Men between 40-49 years old were the demographic group most commonly diagnosed with leptospirosis. August and September were the months with highest incidence over the entire study period. The most common serovar observed was Icterohaemorrhagiae, although over a third of cases were diagnosed via polymerase chain reaction alone. The most common sources of exposure reported were travel abroad, farming, and recreational contact with fresh water, the latter being a new exposure compared to previous studies. Overall, a One Health approach would ensure better detection of outbreaks and milder disease. Additionally, preventative measures should be expanded to include recreational water sports.